Thromboelastometry analysis of thrombocytopenic dengue patients: a cross-sectional study. Issue 1 (December 2017) - Piza, Felipe; Corrêa, Thiago; Marra, Alexandre; Guerra, João; Rodrigues, Roseny; Villarinho, Andrea; de Aranda, Valdir; Shiramizo, Sandra; de Lima, Maria; Kallas, Esper; Cavalcanti, Alexandre
Abstract Background Dengue virus infection (DVI) is a prevalent and potentially fatal viral disease associated with coagulopathy. So far, the coagulation profile of DVI patients with thrombocytopenia has not been assessed through a viscoelastic test such as rotational thromboelastometry. We aimed to describe the prevalence and characteristics of coagulation abnormalities in dengue fever outpatients with thrombocytopenia, addressed by both rotational thromboelastometry and conventional coagulation tests. Methods This was a cross-sectional study conducted between April 6th and May 5th 2015 in São Paulo, Brazil during a dengue outbreak. Thromboelastometry (ROTEM®) and the conventional coagulation tests prothrombin time (PT), international normalized ratio (INR), activated partial thromboplastin time (aPTT), thrombin time (TT), platelet count and fibrinogen levels were performed in 53 patients with DVI and thrombocytopenia. Results Despite a median interquartile range (IQR) platelet count of 77 (63–88) x 109 /L in DVI patients, conventional coagulation tests and plasma fibrinogen levels were within the normal range. Subjects demonstrated hypocoagulability in 71.7% (38/53) in INTEM and 54.7% (29/53) in EXTEM DVI patients. FIBTEM analyses detected only 5.7% (3/53) with hypocoagulability among this population. The median (IQR) clotting time (CT), clot formation time (CFT) and maximum clot firmness (MCF) on INTEM were, respectively, 177 (160–207) sec, 144 (108–178) sec and 48 (42–52) mm. On EXTEM, median (IQR) CT, CFT and MCF were, respectively, 69 (65–78) sec, 148 (126–198) sec and 49 (44–55) mm. Median (IQR) MCF on FIBTEM was 15 (13–18) mm. Conclusion Thromboelastometry impairment is highly prevalent in DVI patients with thrombocytopenia, particularly in INTEM and EXTEM analyses, while standard coagulation tests are normal in this setting. Clinical implications remain to be established.